2011
DOI: 10.1007/s10725-010-9558-6
|View full text |Cite
|
Sign up to set email alerts
|

Changes in endogenous cytokinin profiles in micropropagated Harpagophytum procumbens in relation to shoot-tip necrosis and cytokinin treatments

Abstract: Changes in cytokinin (CK) profiles and their physiological implications in micropropagated Harpagophytum procumbens [(Burch.) DC. ex Meisn.] tissues in relation to shoot-tip necrosis (STN) and CK treatments were studied. Total CK content was quantified in benzyladenine (BA)-treated necrotic and normal plantlets and in plantlets treated with the CKs BA, meta-topolin (mT) and meta-topolin riboside (mTR) with and without the auxin indole-3-acetic acid (IAA). Generally necrotic shoots yielded more total CK compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Therefore, CKs can form various types of glycosides that can possess different roles. Whereas CK N -glucosides are thought to be terminal products of the irreversible deactivation or a detoxification pathway ( McGaw et al, 1984 ; McGaw and Horgan, 1985 ; Blagoeva et al, 2004 ; Sakakibara, 2006 ; Bairu et al, 2011 ), CK O -glucosides were shown to be reversibly deglycosylated by β-glucosidase action ( Brzobohatý et al, 1993 ; Falk and Rask, 1995 ; Kristoffersen et al, 2000 ) and therefore are thought to serve as inactive storage forms of CKs. UGTs belong to a large multi-gene family ( Mackenzie et al, 1997 ) that deactivates a wide range of molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, CKs can form various types of glycosides that can possess different roles. Whereas CK N -glucosides are thought to be terminal products of the irreversible deactivation or a detoxification pathway ( McGaw et al, 1984 ; McGaw and Horgan, 1985 ; Blagoeva et al, 2004 ; Sakakibara, 2006 ; Bairu et al, 2011 ), CK O -glucosides were shown to be reversibly deglycosylated by β-glucosidase action ( Brzobohatý et al, 1993 ; Falk and Rask, 1995 ; Kristoffersen et al, 2000 ) and therefore are thought to serve as inactive storage forms of CKs. UGTs belong to a large multi-gene family ( Mackenzie et al, 1997 ) that deactivates a wide range of molecules.…”
Section: Introductionmentioning
confidence: 99%
“…CK nucleotides are thought to play a central role in the regulation of cytokinin levels as they are readily converted to both the ribosides precursors and/or directly to the active free base forms [ 33 ]. Cytokinin N-glucosides are considered terminal products of the irreversible active cytokinin deactivation and thus are part of a detoxification pathway for cytokinins [ 76 ], although this idea has been challenged recently [ 35 ]. In contrast, cytokinin O -glucosides were shown to be reversibly glycosylated and, because they are also resistant to cleavage by oxidases [ 77 ], they can act as CK storage forms.…”
Section: Discussionmentioning
confidence: 99%
“…In apple, shoot tip necrosis has been associated with low levels of endogenous hormones (Kataeva et al 1991). Moreover, the incidence of shoot tip necrosis seems to be related to the transport and inner distribution of cytokinins (Bairu et al 2011). Urea derivatives may therefore influence auxin/cytokinin cross-talk through their transport machineries, enabling auxin to reach maximum levels at the root initial cells and at the same time facilitating cytokinin transport towards the apex by a transport system that is not yet completely defined (Durán-Medina et al 2017).…”
Section: Discussionmentioning
confidence: 99%